CircCAMSAP1 promotes hepatocellular carcinoma progression through miR‐1294/GRAMD1A pathway. Issue 8 (23rd January 2021) - Luo, Zongjiang; Lu, Libai; Tang, Qianli; Wei, Wang; Chen, Pengyu; Chen, Yichen; Pu, Jian; Wang, Jianchu
Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers with high prevalence and mortality, and it has brought huge economic and health burden for the world. It is urgent to found novel targets for HCC diagnosis and clinical intervention. Circular RNA (circRNA) has been reported to participate in many cancer progressions including HCC, suggesting that circRNA might paly essential role in HCC initiation and progression. Our study aims to found that potential circRNA participates in HCC development and its underlying molecular mechanisms. We obtained three pairs of HCC tissues and its adjacent normal tissues data from GEO DataSets. MTT, cell colony, EdU, wound‐healing, transwell invasion and mouse xenograft model assays were used to demonstrate the biological functions of circCAMSAP1 in HCC progression. Furthermore, we conducted bioinformatics analysis, AGO2‐RIP, RNA pull‐down and luciferase reporter assays to assess the association of circCAMSAP1‐miR‐1294‐GRAMD1A axis in HCC cells. The expression of circCAMSAP1 was up‐regulated in HCC tissues compared with its adjacent normal tissues. Up‐regulation of circCAMSAP1 promoted HCC biological functions both in vitro and in vivo. The promotive effects of circCAMSAP1 on HCC progression function through miR‐1294/GRAMD1A pathway. CircCAMSAP1 was up‐regulated in HCC tissues, and circCAMSAP1 up‐regulated GRAMD1A expression to promote HCC proliferation, migration and invasion through miR‐1294 . CircCAMSAP1 might be a potential prognosis and therapeutic target for HCC.